2000
DOI: 10.1034/j.1600-0684.2000.290303.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced replication of HIV‐1 in vivo in pigtailed macaques (Macaca nemestrina)

Abstract: Non-human primate models for acquired immunodeficiency syndrome (AIDS) are important for studies of prevention and intervention strategies. Ideally, such models would make use of human immunodeficiency virus type 1 (HIV-1) and animals that are readily available for research. HIV-1 was obtained from an infected macaque, and passaged sequentially in three groups of two Macaca nemestrina neonates each. Evidence for enhanced viral replication was first found in one of the group 2 animals, and in both group 3 anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 11 publications
0
15
1
Order By: Relevance
“…We found that in comparison to RM, PTM progress more rapidly to AIDS-defining illnesses after SIVmac239 infection, but this accelerated rate of disease progression was not attributed to increased peak or set-point plasma viral loads. This is of interest, as previous studies have demonstrated that SHIV, HIV-1, and HIV-2 replicate at extremely high levels in pigtail macaques (3,6,24,42,49), and SIVagm replicates at variable levels (20). However, somewhat lower SIVmac239 replication rates followed by progression to AIDS are consistent with the immunodeficiency that is observed in PTM after infection with SIVsun or SIVhoest, where animals progress to AIDS despite low levels of viremia (4).…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…We found that in comparison to RM, PTM progress more rapidly to AIDS-defining illnesses after SIVmac239 infection, but this accelerated rate of disease progression was not attributed to increased peak or set-point plasma viral loads. This is of interest, as previous studies have demonstrated that SHIV, HIV-1, and HIV-2 replicate at extremely high levels in pigtail macaques (3,6,24,42,49), and SIVagm replicates at variable levels (20). However, somewhat lower SIVmac239 replication rates followed by progression to AIDS are consistent with the immunodeficiency that is observed in PTM after infection with SIVsun or SIVhoest, where animals progress to AIDS despite low levels of viremia (4).…”
Section: Discussionmentioning
confidence: 49%
“…Importantly, in contrast to other nonhuman primate models, PTM are susceptible to many lentiviral infections other than SIV and SHIV, including infection with HIV-1, HIV-2, and simian tropic (stHIV-1) (1,3,6,24,29,42,49,55,60), which makes this model invaluable for vaccination and pathogenesis studies. Furthermore, recent characterization of APOBEC and TRIM5␣ genes in PTM has allowed for the development of minimally chimeric stHIV-1 strains, differing from HIV-1 only in vif genes, that persistently infect PTM due to the TRIMCyp fusion protein which PTM harbor rather than TRIM5 (11,21,60).…”
mentioning
confidence: 99%
“…Based on their geographical distribution and morphology differences, pig-tailed macaques are divided into three species: sunda pig-tailed macaque ( M. nemestrina ), northern pig-tailed macaque ( M. leonina ), and mentawai macaque ( M. pagensis ) (8). The sunda pig-tailed macaques (SPMs) are the most frequently used species for HIV-1 infection (918). …”
Section: Introductionmentioning
confidence: 99%
“…M. nemestrina macaques have also been reported to be susceptible to some HIV-1 isolates (1,(4)(5)(6)(7)19) although this idea remains controversial. These observations led us to examine the TRIM5 gene of M. nemestrina for species-specific differences that may explain the apparent susceptibility of this macaque species to infection with HIV.…”
mentioning
confidence: 99%